Design and content validation of a set of SMS to promote seeking of specialized mental health care within the Allillanchu Project. (31st January 2018) - Toyama, M.; Diez-Canseco, F.; Busse, P.; Del Mastro, I.; Miranda, J. J.
Abstract : Background: The aim of this study was to design and develop a set of, short message service (SMS) to promote specialized mental health care seeking within the framework of the Allillanchu Project. Methods: The design phase consisted of 39 interviews with potential recipients of the SMS, about use of cellphones, and perceptions and motivations towards seeking mental health care. After the data collection, the research team developed a set of seven SMS for validation. The content validation phase consisted of 24 interviews. The participants answered questions regarding their understanding of the SMS contents and rated its appeal. Results: The seven SMS subjected to content validation were tailored to the recipient using their name. The reminder message included the working hours of the psychology service at the patient's health center. The motivational messages addressed perceived barriers and benefits when seeking mental health services. The average appeal score of the seven SMS was 9.0 (SD±0.4) of 10 points. Participants did not make significant suggestions to change the wording of the messages. Conclusions: Five SMS were chosen to be used. This approach is likely to be applicable to other similar low-resource settings, and the methodology used can be adapted to develop SMS for other chronic conditions.